2021
DOI: 10.3389/fncel.2021.740165
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the CYLD Impairs Fear Memory of Mice and Disrupts Neuronal Activity and Synaptic Transmission in the Basolateral Amygdala

Abstract: Fear learning and memory are crucial for animal survival. Abnormal fear memory is a hallmark of many neuropsychiatric disorders. Appropriate neuronal activation and excitability in the basolateral amygdala (BLA) are necessary for the formation of fear memory. The gene cylindromatosis (Cyld), which encodes a lysine-63 deubiquitinase, is expressed in several brain regions including the amygdala. The functions of the cylindromatosis protein (CYLD) in the regulation of the neuronal activity, neural circuits and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
9
2
Order By: Relevance
“…The results implicate an in-built compensatory mechanism in CYLD-deficient mice, of which structural changes (spine loss) caused elevated R in and excitability in PNs [ 36 ]. It is worth noting that the finding of an increased number of APs in the PN of M1 differs from what we have observed in the BLA, where a reduced intrinsic excitability of the principal neurons occurred in the absence of CYLD [ 33 ]. Given that we observed, in the present study, a significantly increased R in , rise time of Aps, and decreased after the hyperpolarization (AHP) of the M1 PNs, which did not occur in the BLA [ 33 ], CYLD may regulate neuronal intrinsic property in a brain area and neuronal type specific manner.…”
Section: Discussioncontrasting
confidence: 82%
“…The results implicate an in-built compensatory mechanism in CYLD-deficient mice, of which structural changes (spine loss) caused elevated R in and excitability in PNs [ 36 ]. It is worth noting that the finding of an increased number of APs in the PN of M1 differs from what we have observed in the BLA, where a reduced intrinsic excitability of the principal neurons occurred in the absence of CYLD [ 33 ]. Given that we observed, in the present study, a significantly increased R in , rise time of Aps, and decreased after the hyperpolarization (AHP) of the M1 PNs, which did not occur in the BLA [ 33 ], CYLD may regulate neuronal intrinsic property in a brain area and neuronal type specific manner.…”
Section: Discussioncontrasting
confidence: 82%
“…Recent studies have shown a decrease in both the frequency of spontaneous excitatory postsynaptic currents and the amplitude of mEPSCs in principal neurons in the basolateral amygdala of Cyld −/− mice ( Li et al, 2021 ). Similarly, we found that the amplitudes of both mEPSCs and AMPAR-mediated eEPSCs were reduced in Cyld −/− MSNs compared to Cyld +/+ MSNs, suggesting a decrease in AMPAR levels at synapses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mouse hippocampal neurons transfected with CYLD M719V show a significantly increased cytoplasmic localization of transactivator regulatory DNA-binding protein 43 (TDP-43) and decreased axonal length ( Dobson-Stone et al, 2020 ). CYLD deficiency causes impaired fear memory, auditory neuropathy, and cognitive inflexibility ( Li et al, 2021 ; Yang et al, 2021 ; Zajicek et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These behavioural phenotypes are correlated with reductions in hippocampal network excitability, long-term potentiation and pyramidal neuron spine numbers ( Colombo et al, 2021 ). Additionally, Cyld knockout impairs amygdala-dependent tone-cued fear memory, as Cyld −/− mice exhibit disrupted neuronal activity and synaptic transmission in the basolateral amygdala and a concomitant impaired fear memory ( Li et al, 2021b ). Cyld knockout mice also have a mild hearing impairment, or auditory neuropathy, perhaps associated with reduced neurite outgrowth ( Yang et al, 2021 ).…”
Section: Cyld In Human Diseasementioning
confidence: 99%